[Supplemental material] Biosynthesis of tetrahydrobenzofuran neolignans in somatic embryos of Ocotea catharinensis - dos Santos, Érica Luiz; Floh, Eny Iochevet Segal; Kato, Massuo Jorge (Eclética Química, 2022)
Somatic embryos of Ocotea catharinensis were used as a model to investigate the biosynthetic pathway of tetrahydrobenzofuran neolignan formation by means of feeding 13C-labelled precursors followed by analysis using MS and 13C NMR. Isotopomers of L-[13C]-phenylalanine administered to embryos were incorporated into tetrahydrobenzofuran neolignans and the analysis of 13C NMR clearly revealed the enriched position of precursors. While feeding a series of putative intermediate including [8–13C]-ferulic acid, [8–13C]-glycoferulic acid, and [8–13C]-coniferyl alcohol were not successful in incorporation to the neolignans, the [8–13C]-coniferyl acetate was detected as an intermediate in the biosynthesis of the neolignan 5’-methoxy-porosin. In the bioconversion assay using the protein fraction from the embryogenic cultures, only the substrate coniferyl acetate was converted into isoeugenol, which together with eugenol, is one of the putative precursors of neolignan formation. These findings support that the tetrahydrobenzofuran neolignans are derived from the oxidative coupling between units of E- isoeugenol and 5’-methoxy-eugenol leading to a regio- and stereospecific products.